AKAD RAHN TASJILY PADA GADAI TANAH PERTANIAN DI PEGADAIAN SYARIAH - Rahmadi Indra Tektona; Dyah Ochtorina Susanti (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: This research is motivated by there is an extension of the collateral object, apart from movable, but also immovable assets including farmland which can be applied using the Rahn Tasjily contract. In this regard, in its implementation, it is necessary to analyze whether Rahn Tasjily's contract on pawning of farmland is in accordance with one of the purpose of Islamic law, namely protection of property (hifz al-mal). The purpose of this research is for seeing and understanding the suitability of the Rahn Tasjily pawning farmland with the objectives of Islamic law (hifz al-mal perspective). Research that uses the normative legal research with the statute approach, and conceptual approach, results in Rahn Tasjily pawning farmland provides benefits and protection of property for farmers (rahin), sharia pawnshop (murtahin), and farmland certificate (marhun), and this is certainly in accordance with one of the objectives of Islamic law, namely protection of property (hifz al-mal).